2018
DOI: 10.1016/j.cub.2018.10.031
|View full text |Cite
|
Sign up to set email alerts
|

A Grow-and-Lock Model for the Control of Flagellum Length in Trypanosomes

Abstract: Highlights d The total amount of IFT material increases linearly during flagellum elongation d Reducing IFT rate by knocking down IFT kinesin motors slows down the growth rate d Increasing IFT rate in a locked flagellum does not lead to further elongation d The locking event is initiated prior to cell division SUMMARY Several models have been proposed to explain how eukaryotic cells control the length of their cilia and flagella.Here, we investigated this process in the protist Trypanosoma brucei, an excellent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 68 publications
5
62
1
Order By: Relevance
“…Previous work showed that when the cell division inhibitor teniposide was applied for 8, 16 or 24hrs, the new flagellum grew to the same length as the old flagellum but never exceeded it. This illustrates an intrinsic locking event was initiated on the new flagellum to prevent further growth before cytokinesis [5]. We reasoned that if Cep164C was involved in the locking mechanism then Cep164C it could accumulate at the base of the new flagellum in these teniposide-treated cells once it had reached the length of the old.…”
Section: Cep164c Accumulates On Locked Flagellamentioning
confidence: 98%
See 2 more Smart Citations
“…Previous work showed that when the cell division inhibitor teniposide was applied for 8, 16 or 24hrs, the new flagellum grew to the same length as the old flagellum but never exceeded it. This illustrates an intrinsic locking event was initiated on the new flagellum to prevent further growth before cytokinesis [5]. We reasoned that if Cep164C was involved in the locking mechanism then Cep164C it could accumulate at the base of the new flagellum in these teniposide-treated cells once it had reached the length of the old.…”
Section: Cep164c Accumulates On Locked Flagellamentioning
confidence: 98%
“…During the next cell cycle, this flagellum becomes the old flagellum and does not increase in length or disassemble whilst an entirely new flagellum grows alongside. A locking mechanism is proposed to prevent the old flagellum from growing any longer or shortening in subsequent cell cycles [5]. Previous work showed that when the cell division inhibitor teniposide was applied for 8, 16 or 24hrs, the new flagellum grew to the same length as the old flagellum but never exceeded it.…”
Section: Cep164c Accumulates On Locked Flagellamentioning
confidence: 99%
See 1 more Smart Citation
“…We termed this a locked axoneme (Bertiaux, Morga, Blisnick, Rotureau, & Bastin, 2018). We termed this a locked axoneme (Bertiaux, Morga, Blisnick, Rotureau, & Bastin, 2018).…”
Section: Cells With Two Temporally Distinct Flagella: Age Discriminmentioning
confidence: 99%
“…The first model implies a modification of the axoneme in such a way that it can undergo neither growth nor shrinkage. We termed this a locked axoneme (Bertiaux, Morga, Blisnick, Rotureau, & Bastin, 2018). This could be achieved by the addition of a cap at the distal end that would prevent incorporation or loss of tubulin.…”
Section: Cells With Two Temporally Distinct Flagella: Age Discriminmentioning
confidence: 99%